Pengaruh Fraud Pentagon terhadap Fraudulent Financial Statement dengan Komite Audit sebagai Variabel Moderasi - Sri Ayem; Dewi Kusuma Wardani; Lu’lu’ul Mas’adah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to examine the factors which can affect the existence of a fraudulent financial statement that adds back the audit committee as a moderating variable in the study. The factors that will be tested in this study are the theory of fraud pentagon which consists of pressure, opportunity, rationalization, competence and arrogance. The research sample used is the infrastructure sector listed on the Indonesia stock exchange for the 2016-2020 period. The sample selection methodused purposive sampling method and produced 25 companies with 125 annual reports that were processed. In this study, the hypothesis used is logistic regression. The results of this study are empirically that pressure effect on fraudulent financial statement, opportunity, rationalization, competence and arrogance have on fraudulent financial statement. the audit committee cannot moderate the influence of pressure, opportunity, rationalization, competence and arrogance on fraudulent financial statements. Keywords: fraud pentagon, fraudulent financial statement